Digital Economy and Health: Does Green Technology Matter in BRICS Economies? - Cuifeng Jiang; Hsuling Chang; Imran Shahzad (Frontiers Media S.A., 2022)
The present study attempts to examine the impact of digitization and green technology on the health outcomes of BRICS countries over the period of 1993-2019. Internet users measure digitalization, and health outcome is determined by life expectancy. The study employed the ARDL estimation approach for empirical investigation of country-specific analysis. GDP per capita and current health expenditures have been incorporated as control variables. The study findings reveal that digitalization results in increasing life expectancy in the long-run in BRICS except for Brazil. While green technology tends to enhance life expectancy in the long-run in Russia and China, it produces an insignificant impact on health outcomes in the short-run. While GDP and health expenditures also improve life expectancy in mostly BRICS economies in the long-run and short-run. Our study provides some policy implications for BRICS nations.